Kepemimpinan Kepala Madrasah dalam Meningkatkan Mutu Pendidikan di MTs. N 1 Makassar - Said, Muhammad; Mappanganro, Mappanganro; Masud, Masdar; Bunyamin, Andi (CV. Creative Tugu Pena, 2022)
This article analyzes the leadership of the Head of MTs N 1 Makassar to improve the quality of education, overcome challenges, and take advantage of opportunities for this purpose. A qualitative descriptive approach was applied to analyze this. Data were collected by using technical triangulation and data source triangulation. From a managerial approach, the Head of MTsN 1 Makassar applies Total Quality Management (TQM), a complete quality improvement management. These efforts can only run effectively if programs can be ensured to be coordinated between departments. To ensure improving the quality of education, input, process, and output are analyzed simultaneously. Efforts to improve the quality of education are increasing human resources (HR) for all madrasah residents through increasing the managerial competence of leaders, the competence of educators and education staff, and the learning revolution. Program updates that can always respond to and anticipate the times. Constraints of a lack of budget and low participation of parents, and the occurrence of the Covid-19 pandemic are challenges that have been successfully turned into opportunities by applying the concept of interconnection. Complete and systematic programs consist of planning, implementation, monitoring and control, evaluation, and follow-up using the principles of Plan, Do, Check, Action (PDCA) through Research-Based Digital Madrasah Programs”. Keywords: School Leadership, Quality Education, Total Quality Management